I got it to zero but im stuck on what to do after that
Method I.
Factor out,
(2y+5)(2y-5) = 0
2y+5 = 0 => y = -5/2
2y-5 = 0 => y = 5/2
Method II.
Isolate y^2,
y^2 = 25/4
Take square roots on both sides,
y = +/- 5/2
I got it to zero but im stuck on what to do after that
Method I.
Factor out,
(2y+5)(2y-5) = 0
2y+5 = 0 => y = -5/2
2y-5 = 0 => y = 5/2
Method II.
Isolate y^2,
y^2 = 25/4
Take square roots on both sides,
y = +/- 5/2
Comments
4y^2 - 25 = 0; add 25 to each side of equation ---> 4y^2 = 25; now, divide each side fo equation by 4 ---> y^2 = 25/4; now, use square root property (i.e., take square roots) ---> y = (+/-)(5/2)